Pemikiran Nasr HÃ¢mid AbÃ» Zayd tentang Fiqh al-TaâwÃ®l wa al-TafsÃ®r - Kholid, Abd (Mutawatir, 2014)
AbÃ» Zayd was born on july 1, 1943 in a village called Tanta, the provincial capital of al-GharbÃ®yah, Egypt. AbÃ» Zayd is very concerned with the study of the Koran. Several important works were written al-IttijÃ¢h al-âAqlÃ® fÃ® al-TafsÃ®r: QadÃ®yat al-MajÃ¢z âind al-Muâtazilah al-WasatÃ®yah and Naqd al-KhitÃ¢b al-DÃ®nÃ®. intellectual adventure AbÃ» Zayd peaked when he wrote a short treatise as one of the main requirement professor appointment at the university of Cairo. AbÃ» Zayd has given the feel of a more powerful, though thatâs not easily penetrate the fortress-establishment of religious understanding which is wrapped in the name of